Lake Placid 2 - Flores, David; Schneider, John.; Sarah Lafleur; Sam McMurray; Chad Collins II; Alicia Ziegler (20th Century Fox USA, 2007)
Years after two 30 foot prehistoric crocodiles are captured and killed in Maine the local sheriff teams up with an EPA agent a female Fish and Wildlife agent and a big game hunter to kill four blood-thirsty offspring of the original killer crocs.
Languages : English, Spanish Subtitles : English, Turkish
Keywords: Horror; SciFi -- Fantasy